(untitled) (Journal of Hama University, 2026)
The current research aims to know the degree of prevalence of Alexithymia among a sample of psychological counseling students at Lattakia University and to know the level of Alexithymia among sample members, in addition to revealing the differences between students in Alexithymia according to the variables of academic year, birth order and gender. The research adopted the descriptive approach and the research community included all psychological counseling students in the first and fifth years at Lattakia University; numbering (425) male and female students, as the scale was distributed to (213) female students, distributed to (156) in the first year and (57) in the fifth year and the gender variable was excluded due to the presence of a small number of males in the first academic years and the sense of Lattakia University. The results showed that (the dimension of difficulty in identifying and recognizing feelings; and the dimension of difficulty in describing feelings) was at a high level with an arithmetic mean of (394) and (4.11) and a relative weight of (78.8%) and (8202%) ; while the two dimensions (few dreams and fantasies and outward directed thinking ) were at an average level with an arithmetic mean of (35) and (32) and a relative weight of (70%) and (664). The results also showed the presence of statistically significant differences at a significance level of 0.05 between the average scores of the sample members of the psychological counseling students and God is a servant of the variables (academic year ; order valley).